A kind of physical sunscreen with light texture and preparation method thereof

By using nano zinc oxide and nano titanium dioxide in physical sunscreen, combined with ingredients such as pentathlon hyaluronic acid, and using ultrasonic dispersion and high-speed shear dispersion emulsification technology, the existing physical sunscreen has solved the problem of heavy texture and low sun protection effect, and achieved efficient and lasting sun protection effect and a light skin feeling.

CN116747144BActive Publication Date: 2025-02-28CHAYAN BIOTECHNOLOGY CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310794423.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-30
Publication Date
2025-02-28
Estimated Expiration
2043-06-30

AI Technical Summary

Technical Problem

Due to the incomplete composition ratio or preparation process of physical sunscreens on the existing market, the sunscreen has a thick texture, sticky and difficult to push away, and the sunscreen effect is not long-lasting, and the skin becomes sensitive after long-term use.

Method used

Nano zinc oxide and nanotitanium dioxide are used as the main sun protection ingredients, and combined with five-fold hyaluronic acid, jojoba seed oil, Houttuynia cordata extract, white water lily extract and black barley extract, physical sunscreen with thin texture and good ductility is prepared through ultrasonic dispersion and high-speed shear dispersion emulsification technology.

Benefits of technology

It has achieved a high-power broad-spectrum sun protection effect, with a sun protection time of up to 12 hours. The skin feels light and not thick, and is naturally not white. It is suitable for sensitive skin and can effectively resist sunburn, tanning, redness, and aging, improving the skin's protective ability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004314535170000121
    Figure BDA0004314535170000121
  • Figure BDA0004314535170000131
    Figure BDA0004314535170000131
  • Figure BDA0004314535170000132
    Figure BDA0004314535170000132
Patent Text Reader

Abstract

The invention provides a physical sunscreen with a light texture and a preparation method thereof. The physical sunscreen comprises the following raw materials: nano zinc oxide, nano titanium dioxide, quintuple hyaluronic acid, jojoba seed oil, houttuynia cordata extract, white water lily extract, black barley extract, glycerin, polydimethylsiloxane, triethoxycaprylylsilane, glycerol palmitate, and sorbitan octanoate. The sunscreen product of the invention can play a high-power broad-spectrum sunscreen effect, adopts a physical sunscreen system, can achieve no need to wait for the onset time, can be applied and sunscreened, has a long-lasting sunscreen effect, is mild and non-irritating to the skin, can be suitable for sensitive skin, plays a sunscreen effect and can also protect the skin, takes a two-pronged approach of one prevention and one protection, and improves the tolerance of fragile skin to resist ultraviolet rays; and has good ductility during use, and the skin feels light and transparent without being heavy, natural and not fake white, and has a good use effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sunscreen creams, and in particular to a light and thin physical sunscreen cream and a preparation method thereof. Background Art

[0002] Ultraviolet rays are composed of short-wave UVC, medium-wave UVB, and long-wave UVA. Among them, UVA accounts for about 4.9% of the sunlight energy and can penetrate into the dermis of the skin, causing skin aging, pigmentation, and darkening of the skin. In severe cases, it can even cause skin cancer. In order to reduce the damage caused by ultraviolet rays to the skin and improve the health of the skin, sunscreen came into being. By applying it on the surface of the skin to block the damage of ultraviolet rays and other light to the skin, it can achieve a protective effect to a certain extent. Most people who are aware of sun protection will apply sunscreen every day, and sunscreen has become a must-have product in daily cosmetics. At present, there are chemical sunscreens and physical sunscreens on the market. Chemical sunscreens mainly use substances containing benzene ring structures to absorb light and convert it into heat energy or fluorescence before releasing it for removal. Chemical sunscreens have good sun protection effects, but they are relatively irritating to the skin, causing skin irritation, inflammation, allergies and other symptoms. Some adverse ingredients can even enter the human blood circulation, and the safety is relatively low. Physical sunscreen mainly uses titanium dioxide and zinc oxide to reflect or scatter ultraviolet rays to protect the skin. It is less irritating to the skin and has a higher safety. However, due to the imperfect composition ratio or preparation process of physical sunscreens on the market, the sunscreens are thick and white, sticky and difficult to spread, and have poor effects and short-lasting sunscreen effects during use. In addition, due to long-term use of sunscreens, the physical and chemical properties of the skin environment will be affected to a certain extent, and the skin will become sensitive after a long period of use. Summary of the invention

[0003] In view of this, the present invention proposes a physical sunscreen with a light texture and a preparation method thereof. The sunscreen of the present invention has good ductility, a light texture and no false whiteness, and effectively improves the sun protection effect of the skin.

[0004] The technical solution of the present invention is achieved in this way:

[0005] A light physical sunscreen, comprising the following raw materials in parts by weight: 15-18 parts of nano zinc oxide, 15-18 parts of nano titanium dioxide, 30-40 parts of quintuple hyaluronic acid, 30-40 parts of jojoba seed oil, 10-15 parts of houttuynia cordata extract, 10-15 parts of white water lily extract, 10-15 parts of black barley extract, 8-10 parts of glycerin, 0.3-0.4 parts of polydimethylsiloxane, 0.2-0.4 parts of triethoxycaprylylsilane, 0.3-0.5 parts of glycerol palmitate, and 0.2-0.4 parts of sorbitan octanoate;

[0006] The five-fold hyaluronic acid includes sodium hyaluronate cross-linked polymer, sodium hyaluronate, hyaluronic acid, hydrolyzed hyaluronic acid, and hydrolyzed sodium hyaluronate.

[0007] Furthermore, the five-fold hyaluronic acid comprises the following raw materials in parts by weight: 12 to 18 parts of sodium hyaluronate cross-linked polymer, 20 to 25 parts of sodium hyaluronate, 30 to 35 parts of hyaluronic acid, 35 to 40 parts of hydrolyzed hyaluronic acid, and 35 to 40 parts of hydrolyzed sodium hyaluronate.

[0008] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: adding a zein solution to a sodium hyaluronate solution and stirring and mixing evenly, then adding a propolis solution and stirring and mixing evenly, filtering, washing the colloid with deionized water for 2 to 3 times, evaporating to remove ethanol, freeze-drying, and crushing to obtain the sodium hyaluronate cross-linked polymer.

[0009] Furthermore, the mass ratio of the sodium hyaluronate solution, the zein solution and the propolis solution is 20-30:8-14:1; the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, so as to prepare a sodium hyaluronate solution with a mass concentration of 20-40%; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, so as to prepare a zein solution with a mass concentration of 30-40%; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, so as to prepare a propolis solution with a mass concentration of 15-20%.

[0010] The preparation method of a light and thin physical sunscreen comprises the following steps:

[0011] S1, adding nano zinc oxide and nano titanium dioxide to an ethanol aqueous solution with a volume ratio of ethanol to water of 2-5:1-2, stirring and mixing, then adding polydimethylsiloxane and triethoxyoctylsilane for ultrasonic dispersion, then centrifuging in a high-speed centrifuge, then washing with anhydrous ethanol and deionized water in turn, finally drying in a vacuum drying oven to constant weight, and then crushing into composite powder with a particle size of 30-100 nm;

[0012] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 10-15w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0013] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0014] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil for ultrasonic dispersion; then adding the mixed solution A in the above step S2, the mixed solution B in the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, and repeating the shear emulsification reaction 2 to 3 times to obtain the target physical sunscreen.

[0015] Furthermore, in the above step S1, the stirring and mixing speed is 600-800 r / min, and the stirring and mixing time is 30-60 min; the ultrasonic dispersion temperature is 40-50° C., the rotation speed is 700-800 r / min, and the dispersion time is 2-3 h.

[0016] Furthermore, in the above step S1, the high-speed centrifugation speed is 4000-6000 r / min, the centrifugation time is 15-18 min; and the vacuum drying temperature is 100-120°C.

[0017] Furthermore, in the above step S4, the ultrasonic dispersion conditions are set to a rotation speed of 1000 to 1200 r / min and an ultrasonic time of 30 to 50 min.

[0018] Furthermore, in the above step S4, the reaction conditions in the high-speed shear dispersing emulsifier are set to a rotation speed of 10000 to 15000 r / min and a reaction time of 4 to 6 min.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The sunscreen product SPF50+, PA++++ of the present invention can play a high-power broad-spectrum sunscreen effect. It adopts a physical sunscreen system, so there is no need to wait for the effective time, and it can protect against the sun as soon as it is applied. At the same time, the sunscreen time is as long as 12 hours, and it can continue to play a protective role as long as it does not fall off; it is mild and non-irritating to the skin, and can be suitable for sensitive skin. While playing a sunscreen role, it can also protect the skin under the interaction of multiple ingredients, reduce the sensitivity of the skin, and take a two-pronged approach of one prevention and one protection to enhance the tolerance of fragile skin to resist ultraviolet rays, and can effectively resist sunburn, tanning, sunburn, and sun aging, and meet various daily and outdoor sunscreen needs; the sunscreen of the present invention has good ductility during use, and the skin feels light and transparent without being heavy, natural and not fake white, and has a good use effect.

[0021] 2. In the present invention, the interaction between nano zinc oxide and nano titanium dioxide can reflect and refract ultraviolet rays, reducing the harm of ultraviolet radiation to the skin. At the same time, nano zinc oxide and nano titanium dioxide can improve their stability after being compounded with other ingredients, and will not penetrate into the skin, which can reduce the burden on the skin. Under the interaction of quintuple hyaluronic acid and black barley extract, it can play a role in water retention and repairing the skin, improving the health of the skin. In the quintuple hyaluronic acid, sodium hyaluronate cross-linked polymer can form a protective film on the epidermis of the skin, reducing external damage to the skin, and can also play a role in water retention and reduce water loss in the skin. Sodium hyaluronate can penetrate into the epidermis and basal layer of the skin, providing sufficient moisture to make the skin smooth; hyaluronic acid can penetrate into the basal layer of the skin and the upper end of the dermis, improving the three-dimensional sense of the skin and improving wrinkles; hydrolyzed hyaluronic acid can penetrate deep into the skin, replenish moisture and improve the texture; hydrolyzed sodium hyaluronate can penetrate into the dermis of the skin and replenish moisture; jojoba seed oil is rich in protein and vitamin D, and the oil it contains is very similar to human body oil, which can improve the cortical balance in the skin, repair the skin and reduce damage; Houttuynia cordata extract and white water lily extract reduce the discomfort of the skin after sun exposure, and Houttuynia cordata extract also has a bactericidal effect, reducing the damage to the skin caused by external microorganisms, and can also improve the storage stability of sunscreen.

[0022] 3. In the process of preparing sodium hyaluronate cross-linked polymer, the present invention compounds sodium hyaluronate with zein and propolis to form a cross-linked network structure, which can improve the stability and film-forming ductility of sodium hyaluronate during use, promote better application of the sunscreen of the present invention during use, and thus form a thinner sunscreen layer.

[0023] 4. In the preparation process of the product of the present invention, nano zinc oxide, nano titanium dioxide, polydimethylsiloxane and triethoxycaprylylsilane are firstly compounded to prepare nano composite powder. The surface energy of nano zinc oxide and nano titanium dioxide is reduced by the action of polydimethylsiloxane and triethoxycaprylylsilane, so as to avoid the phenomenon of agglomeration during use and reduce the heavy feeling of sunscreen. In the preparation process, the nano composite powder is firstly mixed with jojoba seed oil to form an oil phase, and then the nano composite powder is emulsified by high-speed shear dispersion with the remaining water phase material, so that the uniform dispersion of each component in the sunscreen in the system can be improved, and the film is easy to be pushed away during use to form a good ductility, and the skin feels light and transparent without being heavy, natural and not fake white, and the stability of the product can be improved. DETAILED DESCRIPTION

[0024] In order to better understand the technical content of the present invention, specific embodiments are provided below to further illustrate the present invention.

[0025] Unless otherwise specified, the experimental methods used in the embodiments of the present invention are all conventional methods.

[0026] Unless otherwise specified, the materials, reagents, etc. used in the embodiments of the present invention can be obtained from commercial sources.

[0027] Example 1

[0028] The light physical sunscreen of this embodiment is composed of the following raw materials in parts by weight: 15 parts of nano zinc oxide, 15 parts of nano titanium dioxide, 30 parts of quintuple hyaluronic acid, 30 parts of jojoba seed oil, 10 parts of houttuynia cordata extract, 10 parts of white water lily extract, 10 parts of black barley extract, 8 parts of glycerin, 0.3 parts of polydimethylsiloxane, 0.2 parts of triethoxycaprylylsilane, 0.3 parts of glycerol palmitate, and 0.2 parts of sorbitan octanoate; the quintuple hyaluronic acid includes the following raw materials in parts by weight: 12 parts of sodium hyaluronate cross-linked polymer, 20 parts of sodium hyaluronate, 30 parts of hyaluronic acid, 35 parts of hydrolyzed hyaluronic acid, and 35 parts of hydrolyzed sodium hyaluronate;

[0029] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, and the sodium hyaluronate solution with a mass concentration of 20-40% is prepared; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, and the zein solution with a mass concentration of 30-40% is prepared; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, and the propolis solution with a mass concentration of 15-20% is prepared; the sodium hyaluronate solution, the zein solution and the propolis solution are taken according to a mass ratio of 20-30:8-14:1, the zein solution is added to the sodium hyaluronate solution, and the mixture is stirred and mixed evenly, and then the propolis solution is added and stirred and mixed evenly, and the mixture is filtered, and the colloid is washed with deionized water for 2-3 times, and the ethanol is evaporated to remove, and the mixture is freeze-dried and crushed to obtain the sodium hyaluronate cross-linked polymer;

[0030] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0031] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 2:1, stir and mix at a speed of 600r / min for 30min, then add polydimethylsiloxane and triethoxyoctylsilane, heat to 40°C, and perform ultrasonic dispersion at a speed of 700r / min for 2h, then set the speed of a high-speed centrifuge to 4000r / min for high-speed centrifugation for 15min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 100°C to dry to constant weight, and then crush into granules with a composite powder of 30nm in size;

[0032] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 12w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0033] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0034] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1000 r / min for 30 minutes; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions are set to a speed of 10000 r / min, the time is 4 minutes, and the shear emulsification reaction is repeated twice to obtain the target physical sunscreen.

[0035] Example 2

[0036] The light physical sunscreen of this embodiment is composed of the following raw materials in parts by weight: 18 parts of nano zinc oxide, 18 parts of nano titanium dioxide, 40 parts of quintuple hyaluronic acid, 40 parts of jojoba seed oil, 15 parts of houttuynia cordata extract, 15 parts of white water lily extract, 15 parts of black barley extract, 10 parts of glycerin, 0.4 parts of polydimethylsiloxane, 0.4 parts of triethoxycaprylylsilane, 0.5 parts of glycerol palmitate, and 0.4 parts of sorbitan octanoate; the quintuple hyaluronic acid includes the following raw materials in parts by weight: 18 parts of sodium hyaluronate cross-linked polymer, 25 parts of sodium hyaluronate, 35 parts of hyaluronic acid, 40 parts of hydrolyzed hyaluronic acid, and 40 parts of hydrolyzed sodium hyaluronate;

[0037] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, and the sodium hyaluronate solution with a mass concentration of 20-40% is prepared; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, and the zein solution with a mass concentration of 30-40% is prepared; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, and the propolis solution with a mass concentration of 15-20% is prepared; the sodium hyaluronate solution, the zein solution and the propolis solution are taken according to a mass ratio of 20-30:8-14:1, the zein solution is added to the sodium hyaluronate solution, and the mixture is stirred and mixed evenly, and then the propolis solution is added and stirred and mixed evenly, and the mixture is filtered, and the colloid is washed with deionized water for 2-3 times, and the ethanol is evaporated to remove, and the mixture is freeze-dried and crushed to obtain the sodium hyaluronate cross-linked polymer;

[0038] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0039] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 5:2, stir and mix at a speed of 800r / min for 60min, then add polydimethylsiloxane and triethoxyoctylsilane, heat to 50°C, and perform ultrasonic dispersion at a speed of 800r / min for 3h, then set the speed of a high-speed centrifuge to 6000r / min for high-speed centrifugation for 18min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 120°C to dry to constant weight, and then crush into granules with a composite powder of 100nm in size;

[0040] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 15w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0041] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0042] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1200 r / min for 50 min; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions setting the speed to 15000 r / min, the time to 6 min, and repeating the shear emulsification reaction 3 times to obtain the target physical sunscreen.

[0043] Example 3

[0044] The light physical sunscreen of this embodiment is composed of the following raw materials in parts by weight: 17 parts of nano zinc oxide, 18 parts of nano titanium dioxide, 32 parts of quintuple hyaluronic acid, 36 parts of jojoba seed oil, 14 parts of houttuynia cordata extract, 14 parts of white water lily extract, 12 parts of black barley extract, 9 parts of glycerin, 0.35 parts of polydimethylsiloxane, 0.25 parts of triethoxycaprylylsilane, 0.4 parts of glycerol palmitate, and 0.4 parts of sorbitan octanoate; the quintuple hyaluronic acid includes the following raw materials in parts by weight: 16 parts of sodium hyaluronate cross-linked polymer, 23 parts of sodium hyaluronate, 32 parts of hyaluronic acid, 39 parts of hydrolyzed hyaluronic acid, and 36 parts of hydrolyzed sodium hyaluronate;

[0045] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, and the sodium hyaluronate solution with a mass concentration of 20-40% is prepared; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, and the zein solution with a mass concentration of 30-40% is prepared; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, and the propolis solution with a mass concentration of 15-20% is prepared; the sodium hyaluronate solution, the zein solution and the propolis solution are taken according to a mass ratio of 20-30:8-14:1, the zein solution is added to the sodium hyaluronate solution, and the mixture is stirred and mixed evenly, and then the propolis solution is added and stirred and mixed evenly, and the mixture is filtered, and the colloid is washed with deionized water for 2-3 times, and the ethanol is evaporated to remove, and the mixture is freeze-dried and crushed to obtain the sodium hyaluronate cross-linked polymer;

[0046] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0047] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 3:2, stir and mix at a speed of 750r / min for 40min, then add polydimethylsiloxane and triethoxyoctylsilane, heat to 45°C, and perform ultrasonic dispersion at a speed of 750r / min for 3h, then set the speed of a high-speed centrifuge to 5500r / min for high-speed centrifugation for 16min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 120°C to dry to constant weight, and then crush into granules with a size of 60nm composite powder;

[0048] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 14w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0049] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0050] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1150 r / min for 45 minutes; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions setting the speed to 12000 r / min, the time to 4 to 6 minutes, and repeating the shear emulsification reaction 3 times to obtain the target physical sunscreen.

[0051] Example 4

[0052] The light physical sunscreen of this embodiment is composed of the following raw materials in parts by weight: 16 parts of nano zinc oxide, 16 parts of nano titanium dioxide, 38 parts of hyaluronic acid, 33 parts of rapeseed oil, 12 parts of houttuynia cordata extract, 13 parts of white water lily extract, 11 parts of black barley extract, 10 parts of glycerin, 0.3 parts of polydimethylsiloxane, 0.35 parts of triethoxycaprylylsilane, 0.3 parts of glycerol palmitate, and 0.25 parts of sorbitan octanoate; the five-fold hyaluronic acid includes the following raw materials in parts by weight: 13 parts of sodium hyaluronate cross-linked polymer, 24 parts of sodium hyaluronate, 34 parts of hyaluronic acid, 36 parts of hydrolyzed hyaluronic acid, and 38 parts of hydrolyzed sodium hyaluronate;

[0053] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, and the sodium hyaluronate solution with a mass concentration of 20-40% is prepared; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, and the zein solution with a mass concentration of 30-40% is prepared; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, and the propolis solution with a mass concentration of 15-20% is prepared; the sodium hyaluronate solution, the zein solution and the propolis solution are taken according to a mass ratio of 20-30:8-14:1, the zein solution is added to the sodium hyaluronate solution, and the mixture is stirred and mixed evenly, and then the propolis solution is added and stirred and mixed evenly, and the mixture is filtered, and the colloid is washed with deionized water for 2-3 times, and the ethanol is evaporated to remove, and the mixture is freeze-dried and crushed to obtain the sodium hyaluronate cross-linked polymer;

[0054] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0055] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 4:1, stir and mix at a speed of 700r / min for 50min, then add polydimethylsiloxane and triethoxyoctylsilane and heat to 48°C, perform ultrasonic dispersion at a speed of 700r / min for 2.5h, then set the speed of a high-speed centrifuge to 4500r / min for high-speed centrifugation for 17min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 110°C to dry to constant weight, and then crush into granules to obtain a composite powder with a particle size of 50nm;

[0056] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 10 w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0057] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0058] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1100 r / min for 40 minutes; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions setting the speed to 14000 r / min, the time to 5 minutes, and repeating the shear emulsification reaction twice to obtain the target physical sunscreen.

[0059] Example 5

[0060] The light physical sunscreen of this embodiment comprises the following raw materials in parts by weight: 18 parts of nano zinc oxide, 17 parts of nano titanium dioxide, 35 parts of quintuple hyaluronic acid, 38 parts of jojoba seed oil, 13 parts of houttuynia cordata extract, 11 parts of white water lily extract, 14 parts of black barley extract, 8 parts of glycerin, 0.4 parts of polydimethylsiloxane, 0.3 parts of triethoxycaprylylsilane, 0.35 parts of glycerol palmitate, 0.35 parts of sorbitan octanoate, and the balance is water; the quintuple hyaluronic acid comprises the following raw materials in parts by weight: 15 parts of sodium hyaluronate cross-linked polymer, 22 parts of sodium hyaluronate, 33 parts of hyaluronic acid, 37 parts of hydrolyzed hyaluronic acid, and 37 parts of hydrolyzed sodium hyaluronate;

[0061] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0062] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 5:2, stir and mix at a speed of 650r / min for 35min, then add polydimethylsiloxane and triethoxyoctylsilane, heat to 42°C, and perform ultrasonic dispersion at a speed of 800r / min for 2h, then set the speed of a high-speed centrifuge to 5000r / min for high-speed centrifugation for 15min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 100°C to dry to constant weight, and then crush into granules to obtain a composite powder with a particle size of 80nm;

[0063] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 10 w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0064] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0065] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1050 r / min for 35 minutes; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions setting the speed to 13000 r / min, the time to 6 minutes, and repeating the shear emulsification reaction 3 times to obtain the target physical sunscreen.

[0066] Comparative Example 1

[0067] The difference between this comparative example and Example 1 is that jojoba seed oil and quintuple hyaluronic acid are missing, and 33 parts of rapeseed oil and 38 parts of hyaluronic acid are added.

[0068] The light physical sunscreen of this comparative example is composed of the following raw materials in parts by weight: 16 parts of nano zinc oxide, 16 parts of nano titanium dioxide, 38 parts of hyaluronic acid, 33 parts of rapeseed oil, 12 parts of houttuynia cordata extract, 13 parts of white water lily extract, 11 parts of black barley extract, 10 parts of glycerin, 0.3 parts of polydimethylsiloxane, 0.35 parts of triethoxycaprylylsilane, 0.3 parts of glycerol palmitate, and 0.25 parts of sorbitan octanoate;

[0069] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0070] S1, take nano zinc oxide and nano titanium dioxide, add them to an ethanol aqueous solution with a volume ratio of ethanol to water of 4:1, stir and mix at a speed of 700r / min for 50min, then add polydimethylsiloxane and triethoxyoctylsilane and heat to 48°C, perform ultrasonic dispersion at a speed of 700r / min for 2.5h, then set the speed of a high-speed centrifuge to 4500r / min for high-speed centrifugation for 17min, then wash with anhydrous ethanol and deionized water in turn, finally place in a vacuum drying oven and set the drying temperature to 110°C to dry to constant weight, and then crush into granules to obtain a composite powder with a particle size of 50nm;

[0071] S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 10 w / t% quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A;

[0072] S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B;

[0073] S4, adding the composite powder prepared in the above step S1 to jojoba seed oil and performing ultrasonic dispersion at a speed of 1100 r / min for 40 minutes; then adding the mixed solution A of the above step S2, the mixed solution B of the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, the reaction conditions setting the speed to 14000 r / min, the time to 5 minutes, and repeating the shear emulsification reaction twice to obtain the target physical sunscreen.

[0074] Comparative Example 2

[0075] The difference between this comparative example and Example 4 is that the method for preparing the sunscreen is different.

[0076] The light physical sunscreen of this embodiment is composed of the following raw materials in parts by weight: 16 parts of nano zinc oxide, 16 parts of nano titanium dioxide, 38 parts of hyaluronic acid, 33 parts of rapeseed oil, 12 parts of houttuynia cordata extract, 13 parts of white water lily extract, 11 parts of black barley extract, 10 parts of glycerin, 0.3 parts of polydimethylsiloxane, 0.35 parts of triethoxycaprylylsilane, 0.3 parts of glycerol palmitate, and 0.25 parts of sorbitan octanoate; the five-fold hyaluronic acid includes the following raw materials in parts by weight: 13 parts of sodium hyaluronate cross-linked polymer, 24 parts of sodium hyaluronate, 34 parts of hyaluronic acid, 36 parts of hydrolyzed hyaluronic acid, and 38 parts of hydrolyzed sodium hyaluronate;

[0077] The preparation method of the sodium hyaluronate cross-linked polymer is as follows: the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30%, and the sodium hyaluronate solution with a mass concentration of 20-40% is prepared; the zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30%, and the zein solution with a mass concentration of 30-40% is prepared; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80%, and the propolis solution with a mass concentration of 15-20% is prepared; the sodium hyaluronate solution, the zein solution and the propolis solution are taken according to a mass ratio of 20-30:8-14:1, the zein solution is added to the sodium hyaluronate solution, and the mixture is stirred and mixed evenly, and then the propolis solution is added and stirred and mixed evenly, and the mixture is filtered, and the colloid is washed with deionized water for 2-3 times, and the ethanol is evaporated to remove, and the mixture is freeze-dried and crushed to obtain the sodium hyaluronate cross-linked polymer;

[0078] The preparation method of the light and thin physical sunscreen comprises the following steps:

[0079] S1, mixing quintuple hyaluronic acid and glycerin and adding them into deionized water, and then adding Houttuynia cordata extract, white water lily extract and black barley extract to dissolve into a mixed solution;

[0080] S2, adding nano zinc oxide, nano titanium dioxide, polydimethylsiloxane, and triethoxycaprylylsilane to jojoba seed oil and performing ultrasonic dispersion for 30 minutes at a speed of 1000 r / min; then adding the mixed solution A of the above step S2, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersion emulsifier. The reaction conditions are set to a speed of 10000 r / min and a time of 4 minutes. The shear emulsification reaction is repeated twice to obtain the target physical sunscreen.

[0081] Sunscreen performance test

[0082] The test was conducted in accordance with relevant standards such as the 2015 edition of the "Technical Specification for Safety of Cosmetics", GB / T 29665-2013 "Skin Care Emulsions" and QB / T1857 "Skin Care Creams".

[0083] (1) Appearance indicators, visual observation

[0084] (2) Centrifugation test: Place the sunscreen sample in a centrifuge tube for centrifugation at a speed of 3000 r / min and a centrifugation time of 30 min. After centrifugation, observe whether the sunscreen lotion has stratification.

[0085] (3) Heat resistance: Keep the sunscreen sample at 39-41°C for 24 hours. After returning to room temperature, observe whether the sunscreen has water-oil separation.

[0086] (4) Cold resistance: Keep the sunscreen samples at -6 to -10°C for 24 hours. After returning to room temperature, observe whether there is any significant difference between before and after the test.

[0087] (5) Sun protection index test: Use UV-2000S sun protection performance analyzer to measure SPF value and PA value.

[0088] (6) Smear test: After applying the sunscreen sample, sensory evaluation and scoring were performed, with a total score of 100 points. The parameters and scoring criteria are shown in Table 1 below.

[0089] Table 1 Sensory evaluation parameters and standards

[0090]

[0091]

[0092] The sunscreen test samples are the sunscreens prepared in Examples 1 to 5 of the present invention and Comparative Examples 1 to 3, and the test results are shown in Table 2 below.

[0093] Table 2 Test results of sunscreen physical and chemical indicators

[0094]

[0095]

[0096] The above results show that the physical sunscreen SPF50+, PA++++ prepared by the present invention can play a high-power broad-spectrum sunscreen effect, has a good sunscreen effect, and the product performance of the present invention is stable, the skin feels light and transparent when used, not heavy, natural and not fake white, and the use effect is good. In Comparative Example 1, the sunscreen that does not contain jojoba seed oil and five-fold hyaluronic acid has poor performance. From Comparative Example 2, it can be found that by compounding nano zinc oxide, nano titanium dioxide with polydimethylsiloxane and triethoxyoctylsilane to prepare nano composite powder, its stability can be improved, agglomeration can be reduced, and the sunscreen effect can be improved. At the same time, the heavy feeling of the sunscreen can also be reduced, and it is naturally not fake white.

[0097] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A light physical sunscreen, characterized in that: The invention is prepared from the following raw materials in parts by weight: 15-18 parts of nano zinc oxide, 15-18 parts of nano titanium dioxide, 30-40 parts of quintuple hyaluronic acid, 30-40 parts of jojoba seed oil, 10-15 parts of houttuynia cordata extract, 10-15 parts of white water lily extract, 10-15 parts of black barley extract, 8-10 parts of glycerin, 0.3-0.4 parts of polydimethylsiloxane, 0.2-0.4 parts of triethoxycaprylylsilane, 0.3-0.5 parts of glycerol palmitate, and 0.2-0.4 parts of sorbitan octanoate; The five-fold hyaluronic acid includes sodium hyaluronate cross-linked polymer, sodium hyaluronate, hyaluronic acid, hydrolyzed hyaluronic acid, and hydrolyzed sodium hyaluronate; The preparation method of the sodium hyaluronate cross-linked polymer is as follows: adding a zein solution to a sodium hyaluronate solution and stirring and mixing uniformly, then adding a propolis solution and stirring and mixing uniformly, filtering, washing the jelly with deionized water for 2 to 3 times, evaporating to remove ethanol, freeze-drying, and then crushing to obtain the sodium hyaluronate cross-linked polymer; The method for preparing the light and thin physical sunscreen comprises the following steps: S1, adding nano zinc oxide and nano titanium dioxide to an ethanol aqueous solution with a volume ratio of ethanol to water of 2-5:1-2, stirring and mixing, then adding polydimethylsiloxane and triethoxyoctylsilane for ultrasonic dispersion, then centrifuging in a high-speed centrifuge, then washing with anhydrous ethanol and deionized water in turn, finally drying in a vacuum drying oven to constant weight, and then crushing into composite powder with a particle size of 30-100 nm; S2, dissolving quintuple hyaluronic acid in deionized water to prepare a 10-15 wt % quintuple hyaluronic acid solution, and then stirring and mixing with glycerol to form a mixed solution A; S3, adding Houttuynia cordata extract, white water lily extract, and black barley extract into deionized water and dissolving them into a mixed solution B; S4, adding the composite powder prepared in the above step S1 to jojoba seed oil for ultrasonic dispersion; then adding the mixed solution A in the above step S2, the mixed solution B in the above step S3, glycerol palmitate, and sorbitan octanoate, and performing a shear emulsification reaction in a high-speed shear dispersing emulsifier, and repeating the shear emulsification reaction 2 to 3 times to obtain the target physical sunscreen.

2. The light physical sunscreen according to claim 1, characterized in that: The five-fold hyaluronic acid comprises the following raw materials in parts by weight: 12 to 18 parts of sodium hyaluronate cross-linked polymer, 20 to 25 parts of sodium hyaluronate, 30 to 35 parts of hyaluronic acid, 35 to 40 parts of hydrolyzed hyaluronic acid, and 35 to 40 parts of hydrolyzed sodium hyaluronate.

3. The light physical sunscreen according to claim 1, characterized in that: The invention is prepared from the following raw materials in parts by weight: 16 parts of nano zinc oxide, 16 parts of nano titanium dioxide, 38 parts of quintuple hyaluronic acid, 33 parts of jojoba seed oil, 12 parts of houttuynia cordata extract, 13 parts of white water lily extract, 11 parts of black barley extract, 10 parts of glycerin, 0.3 parts of polydimethylsiloxane, 0.35 parts of triethoxycaprylylsilane, 0.3 parts of glycerol palmitate and 0.25 parts of sorbitan octanoate.

4. The light physical sunscreen according to claim 1, characterized in that: The mass ratio of the sodium hyaluronate solution, the zein solution and the propolis solution is 20-30:8-14:1; the sodium hyaluronate solution is prepared by adding sodium hyaluronate to a sodium hydroxide solution with a mass concentration of 20-30% to prepare a sodium hyaluronate solution with a mass concentration of 20-40%; The zein solution is prepared by dissolving zein in an ethanol solution with a mass concentration of 25-30% to prepare a zein solution with a mass concentration of 30-40%; the propolis solution is prepared by dissolving propolis in an ethanol solution with a mass concentration of 65-80% to prepare a propolis solution with a mass concentration of 15-20%.

5. The light physical sunscreen according to claim 1, characterized in that: In the above step S1, the stirring and mixing speed is 600-800 r / min, and the stirring and mixing time is 30-60 min; the ultrasonic dispersion temperature is 40-50° C., the rotation speed is 700-800 r / min, and the dispersion time is 2-3 h.

6. The light physical sunscreen according to claim 1, characterized in that: In the above step S1, the high-speed centrifugation speed is 4000-6000 r / min, the centrifugation time is 15-18 min; and the vacuum drying temperature is 100-120°C.

7. The light physical sunscreen according to claim 1, characterized in that: In the above step S4, the rotation speed of the ultrasonic dispersion is 1000-1200 r / min, and the ultrasonic time is 30-50 min; the setting speed in the high-speed shear dispersion emulsifier is 10000-15000 r / min, and the time is 4-6 min.

Citation Information

Patent Citations

  • Refreshing and lasting sunscreen cream and preparation method thereof

    CN111870551A

  • Natural plant sunscreen cream and preparation method thereof

    CN114306191A